Preparation method of easy-to-demould concrete test mould with super-hydrophobic and super-smooth inner wall

By preparing a superhydrophobic/superslippery surface on the inner wall of the concrete mold, the problem of difficult demolding was solved, and the complete and non-destructive demolding of concrete and the efficient use of the mold were achieved.

CN121007757APending Publication Date: 2025-11-25TAISHAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511089387.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-10-18
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

Existing concrete molds tend to stick to concrete during demolding, making demolding difficult. Common methods such as detachable molds are inefficient, release agents affect concrete quality, or require additional tools that can damage the molds.

Method used

A superhydrophobic/superslippery surface was prepared on the inner wall of a concrete mold. The micro-nano structure was formed by combining photolithography, vacuum evaporation deposition and chemical immersion. Lubricating oil was then injected to reduce the adhesion between the concrete and the inner wall of the mold.

Benefits of technology

This method enables easy demolding of concrete, avoids damage to specimens, improves work efficiency, reduces cleaning work, and enhances the durability and protective effect of the mold.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121007757A_ABST
    Figure CN121007757A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an easy-to-demold concrete test mold with super-hydrophobic and super-smooth inner wall, and belongs to the field of concrete test molds. The method comprises the following steps of: a, spin-coating negative photoresist, and obtaining a substrate with an inverted trapezoidal micron structure on the inner wall in an ultraviolet lithography manner; b, depositing a metal layer through vacuum evaporation; c, removing the metal layer on the upper surface of the inverted trapezoidal micron structure on the inner wall of the substrate; d, obtaining a micro-nano hierarchical structure on the metal layer; e, spin-coating molten wax, and after cooling, filling the micron-sized pores with solid wax; f, depositing aluminum through vacuum evaporation, and performing anodic oxidation to obtain a porous metal aluminum surface; g, solid wax is discharged, lubricating oil is injected, the whole pores are filled with the lubricating oil, and the super-hydrophobic and super-smooth surface is obtained; and h, splicing the base to obtain the easy-to-demould concrete test mould with super-hydrophobic and super-smooth performance. The cohesiveness of the concrete and the inner wall of the test mold is reduced, so that the concrete is easily separated from the inner wall of the concrete test mold.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of concrete test mould, in particular to a preparation method of an easy-to-demould concrete test mould with super-hydrophobic and super-slippery inner wall. BACKGROUND

[0002] Concrete generally refers to a kind of artificial stone formed by using cement as cementitious material, sand or gravel as aggregate and adding a certain amount of water, uniformly stirring, compacting, curing and hardening, and is a commonly used civil engineering composite material. In the practical application of concrete, the strength and durability of concrete are key factors affecting the engineering quality. Therefore, it is particularly important to use standard concrete test blocks to test the strength of concrete before construction.

[0003] The concrete test mould is a mould for making standard concrete test blocks required for testing the mechanical strength and durability of concrete, and is mainly divided into a concrete compression test mould, a concrete bending test mould, a concrete axial compression test mould, a concrete axial tension test mould and a concrete splitting tension test mould. At present, the commonly used concrete test mould is divided into two types. One is an integrated concrete test mould formed by four vertical plates and a bottom plate fixed as a whole, which is mostly made of plastic material. The other is a detachable concrete test mould composed of a bottom mould plate, a side mould plate, a partition plate shaft, a support hinge bolt and a butterfly nut, which is mostly made of cast iron or steel.

[0004] When the concrete test piece is made, the hydration process of cement produces hydration products with cementitious properties, which increases the friction between the concrete and the inner wall of the mould, making the concrete easily stick to the inner wall of the mould, making it difficult to demould the concrete, and even causing damage to the concrete test piece after demoulding.

[0005] In order to solve the problem of difficult demoulding of the concrete test piece after forming, there are generally the following treatment methods in the prior art:

[0006] (1) A detachable concrete mould is used, but there is still a large friction between the detachable mould plate and the concrete, and the concrete is easily adhered to the mould plate during demoulding, resulting in incomplete concrete test blocks after demoulding. In addition, the detachable mould needs to be installed before each use, which leads to low work efficiency. In addition, the residual concrete adhered to the mould plate needs to be cleaned in time, which wastes manpower and resources.

[0007] (2) A release agent is coated on the inner wall of the mould; the release agent needs to be coated on the inner wall of the mould in advance when preparing the concrete test block, which reduces the work efficiency. In addition, the release agent makes the surface of the concrete dull, easily adsorbs bubbles, increases the surface tension of the bubbles, and the bubbles are not easy to break and discharge, which easily leaves a large number of bubble cavities on the surface of the concrete. In addition, the release agent is an oily liquid, which is easy to adsorb impurities when stored, which is not conducive to the cleaning of the mould.

[0008] (3) using a release tool or knocking to release the concrete; this method is easy to cause damage to the concrete test block and the mold itself, and also reduces work efficiency. SUMMARY

[0009] In view of the above technical problems, the present application provides an easy-release concrete test mold with super-hydrophobic inner walls, and a preparation method thereof.

[0010] The technical solution adopted by the present application is as follows:

[0011] An easy-release concrete test mold with super-hydrophobic inner walls, comprising four vertical plates and a bottom plate, the inner walls of the vertical plates and the bottom plate are provided with super-hydrophobic surface structures.

[0012] Preferably, the super-hydrophobic surface structure is a micro-nano structure.

[0013] A preparation method of an easy-release concrete test mold with super-hydrophobic inner walls, comprising the following steps:

[0014] a. spin-coating a negative photoresist, and obtaining a substrate with inverted-trapezoidal microstructures on the inner walls by means of ultraviolet lithography;

[0015] b. vacuum evaporation deposition of a metal layer

[0016] metal plating film on the substrate with inverted-trapezoidal microstructures; after plating is completed, the substrate with inverted-trapezoidal microstructures after metal evaporation is taken out;

[0017] c. removing the metal layer on the upper surface of the inverted-trapezoidal microstructures on the inner walls of the substrate;

[0018] d. obtaining a micro-nano hierarchical structure on the metal layer coated by the inverted-trapezoidal microstructures on the inner walls of the substrate by chemical soaking;

[0019] e. spin-coating molten wax on the substrate after step d, and after cooling to room temperature, the solid wax fills into the micron-level pores between the inverted-trapezoidal structures;

[0020] f. spin-coating a positive photoresist and performing ultraviolet lithography;

[0021] g. discharging the solid wax in the micron-level pores to obtain a substrate with super-hydrophobic surface structures;

[0022] h. assembling the substrate to obtain an easy-release concrete test mold with super-hydrophobic properties.

[0023] Preferably, step a specifically comprises the following steps:

[0024] a1, the vertical plate or the bottom plate is used as a substrate, and the substrate is sequentially cleaned with acetone, ethanol and deionized water;

[0025] a2, a layer of negative photoresist is spin-coated on the inner wall surface of the substrate;

[0026] a3, the first inclined UV lithography is performed by using a UV light source.

[0027] a4, the UV light source is rotated by 180°, and the second inclined UV lithography is performed.

[0028] a5, after the lithography is completed, the substrate is immediately placed in a developing solution matched with the negative photoresist for developing, then washed with deionized water and dried, thereby obtaining a substrate with an inverted trapezoidal microstructure on the inner wall.

[0029] Preferably, when the inclined UV lithography is performed, a mirror is placed opposite the UV light source to make the UV light inclinedly irradiate on the UV photoresist, thereby completing the first UV lithography; then the UV light source and the mirror are synchronously rotated by 180°, thereby performing the second UV lithography.

[0030] Preferably, in step b, the metal layer deposited is Mg, Zn, Cu or Al.

[0031] Preferably, in step c, the chemical etching method is used to remove the metal layer on the upper surface of the inverted trapezoidal microstructure.

[0032] First, a nitric acid solution is prepared, then the substrate with the inverted trapezoidal structure is placed horizontally with one side downward, and slowly translated downward, when the substrate just contacts the nitric acid solution, it is kept stationary, so that the metal layer on the upper surface of the inverted trapezoidal microstructure can contact the nitric acid solution, while the metal layer on the side surface does not contact the nitric acid solution; after the reaction is completed, the substrate is washed with deionized water and dried.

[0033] Preferably, in step d, the substrate is placed in a silver nitrate solution or a copper chloride solution, after the reaction, the substrate is taken out, washed with deionized water and dried in air, thereby obtaining a micro-nano structure on the metal layer on the side surface of the inverted trapezoidal structure.

[0034] Specifically, if the deposited metal is Cu, Mg, Zn or the like, the substrate is placed in a silver nitrate solution, the concentration of the silver nitrate solution is 0.01-0.1 mol / L, after the reaction for 1-10 min, the substrate is slowly taken out, washed with deionized water and dried in air, thereby obtaining a dendritic micro-nano hierarchical structure on the metal layer on the side surface of the inverted trapezoidal structure.

[0035] If the vapor-deposited metal is aluminum, the substrate is placed in a copper chloride solution with a concentration of 1-2 mol / L (or a hydrochloric acid solution with a concentration of 1-2 mol / L), reacted for 60 seconds, and then slowly removed. It is then immediately ultrasonically cleaned with deionized water and dried in air to obtain a micro-nano-scale stepped structure on the metal layer on the side of the inverted trapezoidal structure.

[0036] Preferably, after obtaining the micro / nano structure on the metal layer on the side of the inverted trapezoidal structure, a low surface energy modification step is further included: the substrate with the micro / nano structure obtained on the metal layer on the side of the inverted trapezoidal structure is placed in a mixed solution of stearic acid and ethanol for hydrophobic modification treatment, and then rinsed with deionized water and dried, thus obtaining a superhydrophobic micro / nano structure on the inner surface of the micron-scale inverted trapezoid.

[0037] Preferably, in step g: the wax in the micron-sized pores is completely removed by ultrasonic vibration. Specifically, the substrate after the second ultraviolet lithography is placed in an ultrasonic cleaner; the ultrasonic cleaner is started, so that the wax inside the micron structure (i.e., between the inverted trapezoidal structures) gradually melts and is discharged with water by ultrasonic vibration.

[0038] Another object of the present invention is to provide an easy-to-demold concrete mold with superhydrophobic / superslippery inner wall, and a method for preparing the easy-to-demold concrete mold.

[0039] An easy-to-demold concrete test mold with superhydrophobic / superslippery inner wall includes four vertical plates and one bottom plate. The inner walls of the vertical plates and the bottom plate are provided with micro-nano structures, and lubricating oil is injected into the pores of the micro-nano structures.

[0040] The above-mentioned method for preparing easily demolded concrete molds with superhydrophobic / superslippery properties also uses steps a-g, the difference being that it further includes step j: injecting lubricating oil into the substrate with the superhydrophobic surface structure to fill the entire pore to obtain a superslippery surface. Then, the substrate is assembled to obtain the easily demolded concrete mold with superhydrophobic / superslippery properties.

[0041] The third objective of this invention is to provide a method for preparing an easy-to-demold concrete mold with a superhydrophobic inner wall, comprising the following steps:

[0042] First, repeat steps a through e above;

[0043] Then, after filling with solid wax, instead of spin coating with positive photoresist, aluminum is deposited by vacuum evaporation, followed by anodizing to obtain a porous aluminum surface. Finally, the wax in the micron-sized pores is completely removed by ultrasonic vibration to obtain a superhydrophobic surface.

[0044] The above method, specifically the vacuum evaporation deposition of aluminum, includes the following steps:

[0045] The substrate is fixed on the substrate stage, and an aluminum target is placed in the evaporation boat; then the parameters are set and the coating operation begins; after the coating is completed, the aluminum-coated substrate is removed.

[0046] The above method specifically includes the following steps:

[0047] The aluminum-plated substrate was anodized in a phosphoric acid solution with a concentration of 0.1-0.5 mol / L. The aluminum-plated substrate was used as the anode and stainless steel as the cathode, with a distance of 20 mm between the two electrodes. The anodizing voltage was set to 120 V, and the anodizing operation was started at an initial temperature of 50 °C. After the anodizing time lasted for 1-5 min, the anodized aluminum-plated substrate was removed, rinsed with deionized water, and dried in air to obtain anodized aluminum with a porous structure.

[0048] The above method, after anodizing, also includes the following processing steps:

[0049] Anodized aluminum oxide with a porous structure was placed in a mixed solution of stearic acid and ethanol for hydrophobic modification.

[0050] In the above method, the ultrasonic vibration dewaxing step is as follows:

[0051] An anodized aluminum substrate with a porous structure is placed in an ultrasonic cleaner; the ultrasonic cleaner is started, and the wax inside the micron structure gradually melts and is discharged with water under the action of ultrasonic vibration.

[0052] The fourth objective of this invention is to provide a method for preparing an easy-to-demold concrete mold with superhydrophobic / superslippery inner walls. This method employs the aforementioned processing steps, but with the addition of the step of injecting lubricating oil into a substrate with a superhydrophobic surface structure, filling all pores to obtain a superslippery surface. The substrate is then assembled to obtain the easy-to-demold concrete mold with superhydrophobic / superslippery properties.

[0053] The beneficial technical effects of this invention are:

[0054] (1) First, by combining photolithography, vacuum evaporation deposition and chemical immersion, and injecting lubricating oil, a superhydrophobic / superslippery surface is prepared on the inner wall of the concrete mold. The superhydrophobic surface has low adhesion, which reduces the adhesion between the concrete and the inner wall of the mold, making it easy for the concrete to detach from the inner wall of the concrete mold, thus facilitating the complete and undamaged demolding of the concrete.

[0055] (2) The lubricating oil injected into the micro-nano structure has super-slippery properties, which further reduces the adhesion between the concrete and the inner wall of the concrete mold, making it easy to demold the concrete and thus not causing damage to the concrete specimen.

[0056] (3) The micro-nano structure contains lubricating oil, so there is no need to apply release agent in advance when using it, which improves work efficiency.

[0057] (4) The micron-scale inverted trapezoidal structure prepared is a polymer with elasticity. After the concrete is poured, it will be compressed downward under the action of the concrete gravity, thereby squeezing the lubricating oil stored in the micro-nano structure to the surface of the porous structure.

[0058] (5) The obtained micron-scale inverted trapezoidal structure and the micro-nano structure attached to the surface of the micron structure can lock in the lubricating oil and reduce the loss of the lubricating oil, so that the concrete test mold has good durability when used.

[0059] (6) The superhydrophobic / superslippery surface has self-cleaning properties, which can reduce the residual concrete adhering to the inner wall of the concrete mold, thereby keeping the inner wall of the mold clean, reducing daily maintenance and cleaning work, and thus improving work efficiency.

[0060] (7) The rough structure of the superhydrophobic / superslippery surface contains air and lubricating oil respectively, which can effectively isolate external corrosive media. If the concrete mold is metal, the superhydrophobic surface can play a good corrosion protection role for the substrate, thereby enhancing the service life of the concrete mold. Attached Figure Description

[0061] Figure 1 This is a flowchart illustrating the preparation process of the superhydrophobic surface in Example 4;

[0062] Figure 2 This is a top view schematic diagram of a superhydrophobic surface;

[0063] Figure 3 This is a flowchart illustrating the preparation process of the superhydrophobic / superlubricated surface in Example 5;

[0064] Figure 4 This is a top view schematic diagram of a superhydrophobic / superslippery surface.

[0065] In the figure: 1-Concrete test template surface, 2-Negative photoresist, 3-Ultraviolet light source, 4-Reflective lens, 5-Metal layer, 6-Rough micro-nano structure, 7-Wax, 9-Lubricating oil, 10-Metallic aluminum. Detailed Implementation

[0066] To address the problems of existing concrete test molds, such as difficulty in demolding, high adhesion between the mold surface and the concrete, and easy damage to the concrete during demolding, this invention proposes an easy-to-demold concrete test mold with a superhydrophobic / superslippery inner wall.

[0067] 1. By combining ultraviolet lithography, vacuum evaporation deposition technology and chemical immersion method, and injecting lubricating oil, a superhydrophobic / superslippery surface is prepared on the inner wall of the concrete mold, resulting in a concrete mold with low adhesion and easy demolding.

[0068] Second, it makes the inner wall of the concrete mold superhydrophobic, reducing the adhesion of the inner wall of the concrete mold, so that the concrete can be smoothly removed from the formwork during demolding, and the concrete shape can be kept intact.

[0069] Third, the micro-nano structure of the inner wall of the concrete mold helps to lock in the lubricating oil and reduce its loss. In addition, since the micro-nano structure is a polymer with elasticity, after the concrete is poured, the lubricating oil stored in the micro-structure is squeezed out under the pressure of the concrete, which provides a lubricating effect and facilitates the demolding of the concrete.

[0070] Fourth, it enables the concrete test mold to have excellent self-cleaning properties, reduces the residual concrete adhering to the inner wall of the concrete test mold, and improves daily cleaning efficiency.

[0071] The present invention provides an easy-to-demold concrete test mold with superhydrophobic / superslippery inner wall, which has four vertical plates and one bottom plate, and the inner walls of the vertical plates and the bottom plate are all superhydrophobic / superslippery.

[0072] The superhydrophobic / superlubricating surface is obtained by the following steps:

[0073] 1) First, a layer of negative photoresist is spin-coated on the surfaces of the vertical plate and the bottom plate using photolithography. Then, two ultraviolet photolithography processes are performed under an inclined light source to obtain an inverted trapezoidal microstructure.

[0074] 2) Then, a metal layer is deposited on the surface of the inverted trapezoidal microstructure using vacuum evaporation deposition technology;

[0075] 3) Remove the metal layer on the upper surface of the inverted trapezoidal structure using chemical etching;

[0076] 4) Micro-nano hierarchical structures are obtained on the inverted trapezoidal surface by immersion in a chemical solution, and the obtained micro-nano hierarchical structures are further modified by immersion in a low surface energy solution.

[0077] 5) Spin-coat molten wax onto the substrate surface to fill the micron-sized pores;

[0078] 6) After the wax has cured, spin-coat a layer of positive photoresist onto the surface and perform conventional ultraviolet lithography to obtain a micron-scale porous structure;

[0079] 7) Place the substrate after the second UV lithography in an ultrasonic cleaner for ultrasonic cleaning, so that the wax inside the micron structure is discharged with water by ultrasonic vibration, thereby obtaining a superhydrophobic surface.

[0080] 8) Inject lubricating oil into the micro / nano structure to fill the entire pores and obtain an ultra-smooth surface.

[0081] The present invention will be further described below through specific embodiments.

[0082] Example 1

[0083] A method for preparing an easy-to-demold concrete test mold with a superhydrophobic inner wall includes the following steps:

[0084] a. Spin-coating negative photoresist and obtaining a substrate with an inverted trapezoidal micron structure on the inner wall by ultraviolet lithography.

[0085] Step a specifically includes the following steps:

[0086] a1. Use the upright plate or base plate as the base, and clean the base with acetone, ethanol and deionized water in sequence.

[0087] a2. Spin-coat a layer of negative photoresist onto the inner surface of the substrate.

[0088] a3. The first tilted ultraviolet lithography was performed using an ultraviolet light source.

[0089] a4. Rotate the ultraviolet light source 180° and perform a second tilted ultraviolet lithography.

[0090] a5. After photolithography, immediately place the substrate in the developer corresponding to the negative photoresist for development, then rinse with deionized water and dry to obtain a substrate with an inverted trapezoidal micron structure on the inner wall.

[0091] In the above steps, when performing tilted ultraviolet lithography, an ultraviolet light source and a reflective mirror are used, such as... Figure 1 , Figure 3 As shown, a reflective mirror is placed at an angle opposite the ultraviolet light source, allowing the ultraviolet light to shine obliquely onto the ultraviolet photoresist, completing the first ultraviolet lithography. Subsequently, the ultraviolet light source and the reflective mirror are rotated 180° synchronously to perform the second ultraviolet lithography.

[0092] b. Vacuum evaporation deposition of metal layers

[0093] A substrate with an inverted trapezoidal micron structure is subjected to metal deposition. After deposition, the substrate with the inverted trapezoidal micron structure is removed after the metal layer has been evaporated.

[0094] The vapor-deposited metal layer is a Mg, Zn, or Cu metal layer.

[0095] c. Remove the metal layer on the upper surface of the inverted trapezoidal microstructure on the inner wall of the substrate.

[0096] Specifically, a chemical etching method is used to remove the metal layer on the upper surface of the inverted trapezoidal microstructure.

[0097] First, prepare a 6 mol / L nitric acid solution. Then, place the substrate with the inverted trapezoidal structure horizontally downwards and slowly slide it downwards. When the substrate just touches the nitric acid solution, keep it stationary to ensure that the metal layer on the upper surface of the inverted trapezoidal micron-scale structure can contact the nitric acid solution, while the metal layer on the side will not. After reacting for 5 seconds, rinse with deionized water and dry.

[0098] d. A micro-nano hierarchical structure was obtained on the metal layer covered by the inverted trapezoidal micro-structure on the inner wall of the substrate by chemical immersion.

[0099] Specifically, the substrate was placed in a 0.01 mol / L silver nitrate solution, reacted for 5 minutes, then removed, rinsed with deionized water, and dried in air to obtain a dendritic micro / nano hierarchical structure on the metal layer on the side of the inverted trapezoidal structure.

[0100] Then, low surface energy modification was performed: the substrate with micro-nano-scale structure obtained on the metal layer on the side of the inverted trapezoidal structure was placed in a mixed solution of stearic acid and ethanol, with a stearic acid concentration of 0.01 mol / L and a placement time of 60 min for hydrophobic modification treatment. After rinsing with deionized water and drying, a micro-nano-scale structure with superhydrophobicity was obtained on the inner surface of the micron-scale inverted trapezoid.

[0101] e. On the substrate treated in step d, spin-coat molten wax and, after cooling to room temperature, the solid wax fills the micron-sized pores between the inverted trapezoidal structures.

[0102] f. Spin-coat positive photoresist, pre-design the photolithography pattern, and perform conventional ultraviolet lithography. After photolithography, immediately immerse in the developer corresponding to the positive photoresist for development, rinse with deionized water, and dry.

[0103] The aforementioned photolithographic pattern can be any shape, such as square, rectangle, rhombus, circle, or triangle.

[0104] g. Remove the solid wax from the micron-sized pores to obtain a substrate with a superhydrophobic surface structure; specifically, ultrasonic vibration can be used to completely remove the wax from the micron-sized pores.

[0105] The steps are as follows: Place the substrate after the second UV lithography in an ultrasonic cleaner; set the ultrasonic cleaning temperature to 65℃ and the time to 30min; start the ultrasonic cleaner, and the wax inside the micron structure gradually melts and is discharged with water by ultrasonic vibration.

[0106] h. Assemble the base to obtain an easy-to-demold concrete test mold with superhydrophobic properties.

[0107] The substrate can be made of plastic, steel, or other materials.

[0108] The superhydrophobic surface obtained in this embodiment has the following advantages:

[0109] (1) The superhydrophobic surface has low adhesion, which reduces the adhesion between the concrete and the inner wall of the mold, making it easy for the concrete to detach from the inner wall of the concrete mold, thus facilitating the complete and undamaged demolding of the concrete.

[0110] (2) The superhydrophobic surface has self-cleaning properties, which can reduce the residual concrete adhering to the inner wall of the concrete mold, thereby keeping the inner wall of the mold clean, reducing daily maintenance and cleaning work, and thus improving work efficiency.

[0111] (3) The rough structure of the superhydrophobic surface contains an air layer, which reduces the contact area between the external medium and the concrete test mold surface, thereby reducing the friction between the external material and the concrete test mold surface, and can reduce the damage to the inner wall of the concrete test mold during concrete pouring.

[0112] (4) The rough structure of the superhydrophobic surface contains an air layer, which can effectively isolate external corrosive media. If the concrete mold is metal, the superhydrophobic surface can play a good role in corrosion protection of the substrate, thereby enhancing the service life of the concrete mold.

[0113] Example 2

[0114] The preparation method is the same as in Example 1, except that: lubricating oil is injected into the substrate with the superhydrophobic surface structure obtained in step g of Example 1 to fill the entire pores and obtain a super-slippery surface. Then the substrate is assembled to obtain an easy-to-demold concrete mold with superhydrophobic / super-slippery properties.

[0115] This embodiment, through further injection of lubricating oil, yields a superhydrophobic / superslippery surface with the following advantages:

[0116] (1) The lubricating oil injected into the micro-nano structure has super-slippery properties, which further reduces the adhesion between the concrete and the inner wall of the concrete mold, making it easy to demold the concrete and thus not causing damage to the concrete specimen.

[0117] (2) The micro-nano structure contains lubricating oil, so there is no need to apply release agent in advance when using it, which improves work efficiency.

[0118] (3) The micron-scale inverted trapezoidal structure prepared is a polymer with elasticity. After the concrete is poured, it will be compressed downward by the gravity of the concrete, thereby squeezing the lubricating oil stored in the micro-nano structure to the surface of the porous structure.

[0119] (4) The obtained micron-scale inverted trapezoidal structure and the micro-nano structure attached to the surface of the micron structure can lock in the lubricating oil and reduce the loss of the lubricating oil, so that the concrete test mold has good durability when used.

[0120] (5) The super-smooth surface has self-cleaning properties, which can reduce the residual concrete adhering to the inner wall of the concrete mold, thereby keeping the inner wall of the mold clean, reducing daily maintenance and cleaning work, and thus improving work efficiency.

[0121] (6) The rough structure of the super-slippery surface contains lubricating oil, which can effectively isolate external corrosive media. If the concrete mold is metal, the superhydrophobic surface can play a good role in corrosion protection of the substrate, thereby enhancing the service life of the concrete mold.

[0122] (7) The rough structure of the super-slippery surface contains a layer of lubricating oil, which can effectively isolate external corrosive media. If the concrete mold is metal, the super-slippery surface can play a good role in corrosion protection of the substrate, thereby enhancing the service life of the concrete mold.

[0123] (8) The rough structure of the super-smooth surface contains a layer of lubricating oil, which reduces the friction between external substances and the concrete test mold surface, and can reduce the damage to the inner wall of the concrete test mold when pouring concrete.

[0124] Example 3

[0125] The preparation method is the same as in Example 1, except that in step b, the vapor-deposited metal layer is an Al metal layer. Correspondingly, in step d, the substrate is placed in a 1 mol / L copper chloride solution (or a 2 mol / L hydrochloric acid solution), reacted for 60 seconds, and then slowly removed. It is immediately ultrasonically cleaned with deionized water and dried in air to obtain a micro-nano-scale stepped structure on the metal layer on the side of the inverted trapezoidal structure.

[0126] Example 4

[0127] A method for preparing an easy-to-demold concrete test mold with a superhydrophobic inner wall includes the following steps:

[0128] a. Spin-coating negative photoresist and obtaining a substrate with an inverted trapezoidal micron structure on the inner wall by ultraviolet lithography.

[0129] Step a specifically includes the following steps:

[0130] a1. Use the upright plate or base plate as the base, and clean the base with acetone, ethanol and deionized water in sequence.

[0131] a2. Spin-coat a layer of negative photoresist onto the inner surface of the substrate.

[0132] a3. The first tilted ultraviolet lithography was performed using an ultraviolet light source.

[0133] a4. Rotate the ultraviolet light source 180° and perform a second tilted ultraviolet lithography.

[0134] a5. After photolithography, immediately place the substrate in the developer corresponding to the negative photoresist for development, then rinse with deionized water and dry to obtain a substrate with an inverted trapezoidal micron structure on the inner wall.

[0135] In the above steps, when performing tilted ultraviolet lithography, an ultraviolet light source and a reflective mirror are used, such as... Figure 1 , Figure 3 As shown, a reflective mirror is placed at an angle opposite the ultraviolet light source, allowing the ultraviolet light to shine obliquely onto the ultraviolet photoresist, completing the first ultraviolet lithography. Subsequently, the ultraviolet light source and the reflective mirror are rotated 180° synchronously to perform the second ultraviolet lithography.

[0136] b. Vacuum evaporation deposition of metal layers

[0137] A substrate with an inverted trapezoidal micron structure is subjected to metal deposition. After deposition, the substrate with the inverted trapezoidal micron structure is removed after the metal layer has been evaporated.

[0138] The vapor-deposited metal layer is a Mg, Zn, or Cu metal layer.

[0139] c. Remove the metal layer on the upper surface of the inverted trapezoidal microstructure on the inner wall of the substrate.

[0140] Specifically, a chemical etching method is used to remove the metal layer on the upper surface of the inverted trapezoidal microstructure.

[0141] First, prepare a 6 mol / L nitric acid solution. Then, place the substrate with the inverted trapezoidal structure horizontally downwards and slowly slide it downwards. When the substrate just touches the nitric acid solution, keep it stationary to ensure that the metal layer on the upper surface of the inverted trapezoidal micron-scale structure can contact the nitric acid solution, while the metal layer on the side will not. After reacting for 5 seconds, rinse with deionized water and dry.

[0142] d. A micro-nano hierarchical structure was obtained on the metal layer covered by the inverted trapezoidal micro-structure on the inner wall of the substrate by chemical immersion.

[0143] Specifically, the substrate was placed in a 0.01 mol / L silver nitrate solution, reacted for 5 minutes, then removed, rinsed with deionized water, and dried in air to obtain a dendritic micro / nano hierarchical structure on the metal layer on the side of the inverted trapezoidal structure.

[0144] Then, low surface energy modification was performed: the substrate with micro-nano-scale structure obtained on the metal layer on the side of the inverted trapezoidal structure was placed in a mixed solution of stearic acid and ethanol, with a stearic acid concentration of 0.01 mol / L and a placement time of 60 min for hydrophobic modification treatment. After rinsing with deionized water and drying, a micro-nano-scale structure with superhydrophobicity was obtained on the inner surface of the micron-scale inverted trapezoid.

[0145] e. On the substrate treated in step d, spin-coat molten wax and, after cooling to room temperature, the solid wax fills the micron-sized pores between the inverted trapezoidal structures.

[0146] f. A porous metallic aluminum surface is obtained by vacuum evaporation deposition of aluminum followed by anodizing.

[0147] The steps for vacuum evaporation deposition of aluminum are as follows:

[0148] The substrate is fixed on the substrate stage, and an aluminum target is placed in the evaporation boat; then the parameters are set and the coating operation begins; after the coating is completed, the aluminum-coated substrate is removed.

[0149] The anodizing steps are as follows:

[0150] The aluminum-plated substrate was anodized in a 0.25 mol / L phosphoric acid solution, with the aluminum-plated substrate as the anode and stainless steel as the cathode, and the distance between the two electrodes was set to 20 mm. The anodizing voltage was set to 120 V, and the anodizing operation was started at an initial temperature of 50 °C. After the anodizing time lasted for 1 min, the anodized aluminum-plated substrate was removed, rinsed with deionized water, and dried in air to obtain anodized aluminum with a porous structure.

[0151] After anodizing, the sample is placed in an ethanol solution of 0.01 mol / L stearic acid (or silane) for 60 min for hydrophobic modification.

[0152] g. Remove the solid wax from the micron-sized pores to obtain a substrate with a superhydrophobic surface structure. Specifically, ultrasonic vibration can be used to completely remove the wax from the micron-sized pores.

[0153] The steps are as follows: Place the substrate after the second UV lithography in an ultrasonic cleaner; set the ultrasonic cleaning temperature to 65℃ and the time to 30min; start the ultrasonic cleaner, and the wax inside the micron structure gradually melts and is discharged with water by ultrasonic vibration.

[0154] h. Assemble the base to obtain an easy-to-demold concrete test mold with superhydrophobic properties.

[0155] Example 5

[0156] The preparation method is the same as in Example 4, except that: lubricating oil is injected into the substrate with the superhydrophobic surface structure obtained in step g of Example 4 to fill the entire pores and obtain a super-slippery surface. Then the substrate is assembled to obtain an easy-to-demold concrete mold with superhydrophobic / super-slippery properties.

Claims

1. A method for preparing an easy-to-demold concrete test mold with superhydrophobic and super-slippery inner walls, characterized in that, The material comprises four upright plates and one base plate, the inner walls of which are provided with micro / nano structures, and lubricating oil is injected into the pores of the micro / nano structures; the preparation method includes the following steps: a. Spin-coating negative photoresist and obtaining a substrate with an inverted trapezoidal micron structure on the inner wall by ultraviolet lithography; b. Vacuum evaporation deposition of metal layer; A substrate with an inverted trapezoidal micron structure is coated with a metal film; after the coating is completed, the substrate with the inverted trapezoidal micron structure after the metal layer is evaporated is removed. c. Remove the metal layer on the upper surface of the inverted trapezoidal microstructure on the inner wall of the substrate; d. A micro-nano hierarchical structure was obtained on the metal layer covered by the inverted trapezoidal micro-structure on the inner wall of the substrate by chemical immersion. e. On the substrate treated in step d, spin-coat molten wax, and after cooling to room temperature, solid wax fills the micron-sized pores between the inverted trapezoidal structures; f. Vacuum evaporation deposition of aluminum, followed by anodizing to obtain a porous metallic aluminum surface; g. Remove the wax from the micron-sized pores to obtain a substrate with a superhydrophobic surface structure; h: Inject lubricating oil into the substrate with the superhydrophobic surface structure to fill the entire pores to obtain an ultraslippery surface; j: Assemble the substrate to obtain an easy-to-demold concrete test mold with superhydrophobic and ultraslippery properties.

2. The method for preparing an easy-to-demold concrete mold with superhydrophobic and super-slippery inner wall according to claim 1, characterized in that, Step a specifically includes the following steps: a1. Use the upright plate or base plate as the base, and clean the base with acetone, ethanol and deionized water in sequence. a2. Spin-coat a layer of negative photoresist onto the inner wall surface of the substrate; a3. The first tilted ultraviolet lithography was performed using an ultraviolet light source; a4. Rotate the ultraviolet light source 180° to perform a second tilting ultraviolet lithography; a5. After photolithography, the substrate is immediately placed in a developer solution compatible with the negative photoresist phase for development, then rinsed with deionized water and dried to obtain a substrate with an inverted trapezoidal micron structure on the inner wall.

3. The method for preparing an easy-to-demold concrete test mold with superhydrophobic and super-slippery inner wall according to claim 1, characterized in that: When performing tilted ultraviolet lithography, an ultraviolet light source and a reflective mirror are used. A reflective mirror is placed tilted opposite the ultraviolet light source so that the ultraviolet light can shine on the ultraviolet photoresist at an angle, completing the first ultraviolet lithography. Then, the ultraviolet light source and the reflective mirror are rotated 180° synchronously to perform the second ultraviolet lithography.

4. The method for preparing an easy-to-demold concrete test mold with superhydrophobic and super-slippery inner wall according to claim 1, characterized in that, In step b: the vapor-deposited metal layer is a Mg, Zn, Cu or Al metal layer.

5. The method for preparing an easy-to-demold concrete test mold with superhydrophobic and super-slippery inner wall according to claim 1, characterized in that, In step c: the metal layer on the upper surface of the inverted trapezoidal microstructure is removed by chemical etching; first, a nitric acid solution is prepared, then the side of the substrate with the inverted trapezoidal structure is placed horizontally downwards and slowly moved downwards. When the substrate just touches the nitric acid solution, it is kept still to ensure that the metal layer on the upper surface of the inverted trapezoidal microstructure can contact the nitric acid solution, while the metal layer on the side will not contact the nitric acid solution. After the reaction is complete, rinse with deionized water and dry.

6. The method for preparing an easy-to-demold concrete test mold with superhydrophobic and super-slippery inner wall according to claim 1, characterized in that, In step d: the substrate is placed in silver nitrate solution or copper chloride solution, removed after reaction, rinsed with deionized water and dried in air to obtain a micro-nano scale structure on the metal layer on the side of the inverted trapezoidal structure.

7. The method for preparing an easy-to-demold concrete test mold with superhydrophobic and super-slippery inner wall according to claim 6, characterized in that, It also includes a low surface energy modification step: the substrate with micro-nano structure obtained on the metal layer on the side of the inverted trapezoidal structure is placed in a mixed solution of stearic acid and ethanol for hydrophobic modification treatment, and then rinsed with deionized water and dried, thus obtaining a micro-nano structure with superhydrophobicity on the inner surface of the micron-scale inverted trapezoid.

8. The method for preparing an easy-to-demold concrete test mold with superhydrophobic and super-slippery inner wall according to claim 1, characterized in that, In step f, the vacuum evaporation deposition of aluminum specifically includes the following steps: fixing the substrate on the substrate stage and placing the aluminum target in the evaporation boat; then setting the parameters and starting the coating operation; after the coating is completed, removing the aluminum-coated substrate.

9. The method for preparing an easy-to-demold concrete test mold with superhydrophobic and super-slippery inner wall according to claim 1, characterized in that, In step f, the anodizing process specifically includes the following steps: anodizing the aluminum-plated substrate in a phosphoric acid solution with a concentration of 0.1-0.5 mol / L, using the aluminum-plated substrate as the anode and stainless steel as the cathode, with a distance of 20 mm between the two electrodes; setting the anodizing voltage to 120 V and starting the anodizing operation at an initial temperature of 50 °C; after the anodizing time lasts for 1-5 min, removing the anodized aluminum-plated substrate, rinsing it with deionized water, and drying it in air to obtain anodized aluminum with a porous structure.

10. The method for preparing an easy-to-demold concrete test mold with superhydrophobic and super-slippery inner wall according to claim 1, characterized in that, In step g: the wax in the micron-sized pores is completely removed by ultrasonic vibration.